Recognition of foreign qualifications in Denmark - Larsen, Jorgen Ole [Verfasser] (My University, 2012)
"Since 2003 foreigners have legal access to getting their qualification assessed and recognised in Denmark. There are several methods and initiatives to get foreign qualifications recognised. The article describes the legal basis and procedures for the recognition and assessment of foreign qualifications, both for the labour market and for the Danish educational system. Furthermore, it outlines the role ascribed to qualifications in today’s Denmark in the context of the residence permit rule." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2.1 Westeuropa; Auslandsqualifikation; Anerkennung; Verfahren; Dänemark